2020
DOI: 10.4314/jae.v24i1.14
|View full text |Cite
|
Sign up to set email alerts
|

Community participation and sustainability of the community and social development projects in Kwara State, Nigeria

Abstract: The study identified development projects instituted under the CSDP, ascertained extent of community participation at every critical stage of the project and determined whether perceived sustainability of CSDPs was significantly related to community participation in Kwara State. Multistage sampling procedure was used to select 120 respondents for the study. Structured interview schedule was used for data collection while percentages, mean scores and the Pearson Product Moment Correlation (PPMC) were used for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…The quote above is consistent with studies that have shown a significant relationship between indigenous knowledge, community participation and sustainable development (Breidlid, 2009; Sillitoe and Marzano, 2009; Yusuf et al, 2020).…”
Section: Findings and Discussion: Manifestations Of Mainstreaming In Community Developmentsupporting
confidence: 89%
See 1 more Smart Citation
“…The quote above is consistent with studies that have shown a significant relationship between indigenous knowledge, community participation and sustainable development (Breidlid, 2009; Sillitoe and Marzano, 2009; Yusuf et al, 2020).…”
Section: Findings and Discussion: Manifestations Of Mainstreaming In Community Developmentsupporting
confidence: 89%
“…When the indigenous people get to participate in the development process, they perceive such community development projects as theirs whether the process is being driven by sub-national or national development agencies, a view expressed by over 90% of the participants from OTC and ATC traditional and local government areas. This approach has the potential for sustainable community development (Yusuf et al, 2020).…”
Section: Findings and Discussion: Manifestations Of Mainstreaming In Community Developmentmentioning
confidence: 99%
“…Community participation in the local development process is a vital component and a definite approach to accelerate the socio-economic transformation of Nigeria's rural areas, as evidenced in various policy studies [17] [18]. The fact remains that many povertyreduction efforts fail because they were supply-driven and topdown, ignoring community participation and management of development projects [19].…”
Section: Literature Reviewmentioning
confidence: 99%